O pedagogice naszych czasów. Uwagi w związku z "Pismami filozoficznymi" A. Einsteina = On the pedagogy of our times. Considerations embedded in the "Philosophical scriptures" by A. Einstein - Pasterniak, Wojciech (1935-2018) (Zielona Góra: Uniwersytet Zielonogórski)
The author attempts at demonstrating the helplessness and disarray in contemporary pedagogy the light of Einstein's outlook on philosophy and education. The problem of the relationsbetween science, religion and pedagogy has been highlighted in the dissertation.
Keywords: pedagogika; Einstein, Albert (1879-1955)